2019
DOI: 10.1002/cmdc.201900034
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Xanthine Oxidase: Scaffold Diversity and Structure‐Based Drug Design

Abstract: Xanthine oxidase (XO) is the enzyme responsible for the catabolism of purines and their conversion into uric acid. XO is thus the target for the treatment of hyperuricemia and gout. For more than 50 years the only XO inhibitor drug available on the market was the purine analogue allopurinol. In the last decade there has been a resurgence in the search for new inhibitors of XO, as the activity of XO and hyperuricemia have also been associated with a variety of conditions such as diabetes, hypertension, and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 170 publications
0
35
0
Order By: Relevance
“…In addition to these clinically used drugs, over the years, several other molecules with XO inhibitory activity have been described [6][7][8][9]. Despite the existence of some reviews in this topic [6,7,[9][10][11], it is necessary to complement these works with a study focusing on the hit to lead evolution in the development of new XO inhibitors with improved potency and safety when compared with the clinically used drugs. Interestingly, as can be seen in this review, natural molecules and semisynthetic analogues and derivatives constitute a large group of compounds being explored at the moment in this context.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these clinically used drugs, over the years, several other molecules with XO inhibitory activity have been described [6][7][8][9]. Despite the existence of some reviews in this topic [6,7,[9][10][11], it is necessary to complement these works with a study focusing on the hit to lead evolution in the development of new XO inhibitors with improved potency and safety when compared with the clinically used drugs. Interestingly, as can be seen in this review, natural molecules and semisynthetic analogues and derivatives constitute a large group of compounds being explored at the moment in this context.…”
Section: Introductionmentioning
confidence: 99%
“…With the availability of a handful of XO inhibitors in clinical use for treating hyperuricemia, the novel drugs addressing cardiac complications are demanding [70]. Recently, non-purine-like XO inhibitors have drawn significant attention, so they do not interfere with other facets of purine metabolism [48]. XO inhibitors could be equally useful for diabetic patients [71].…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid residues participating in forming Pi-Pi and Pi-cation interactions were also investigated. Amentoflavone (1) and 6-paradol (3) was surrounded by several amino acid residues (Glu 802, Asn 768, Phe 914, ser 876, and Arg 880), which were described as active site residues [48]. It has been reported that Arg 880 and Glu 802 residues play a key role in the hydroxylation of substrate xanthine [49].…”
Section: Xo Molecular Docking Analysismentioning
confidence: 99%
“…The 1,3,5‐triazine ( I ) (Figure ) is a simple, but privileged heterocycle, which has been incorporated as the central core ring in a number of drugs showing, to cite someone, antitumoral, antimicrobial, antiviral, or antimalarial therapeutic potential, among the diverse array of biological activities that this functional motif is able to afford to the molecules that bear it. The fusion of 1,3,5‐triazines with other rings usually results in even more versatile structures . The 1,3,5‐triazine heterocyclic motif is also endowed with electronic properties that have been used with in designing new molecular structures or platforms …”
Section: Figurementioning
confidence: 99%